Assembling Ecological Pieces to Reconstruct the Conservation Puzzle of the Aegean Sea - Sini, Maria; Katsanevakis, Stelios; Koukourouvli, Nikoleta; Gerovasileiou, Vasilis; Dailianis, Thanos; Buhl-Mortensen, Lene; Damalas, Dimitris; Dendrinos, Panagiotis; Dimas, Xenophon; Frantzis, Alexandros; Gerakaris, Vasilis; Giakoumi, Sylvaine; et al. (Frontiers in Marine Science, 2017)
The effective conservation of marine biodiversity through an integrated ecosystem-based management approach requires a sound knowledge of the spatial distribution of habitats and species. Although costly in terms of time and resources, acquiring such information is essential for the development of rigorous management plans and the meaningful prioritization of conservation actions. Located in the northeastern part of the Mediterranean, the Aegean Sea represents a stronghold for marine biodiversity. However, conservation efforts are hampered by the apparent lack of spatial information regarding marine habitats and species. This work is the first to address this knowledge gap by assembling, updating, and mapping information on the distribution of key ecological components. A range of data sources and methodological approaches was utilized to compile and complement the available data on 68 ecological features of conservation interest (58 animal species, 6 habitat categories, and 4 other vulnerable ecological features). A standardized data evaluation procedure was applied, based on five semi-quantitative data quality indicators in the form of a pedigree matrix. This approach assessed the sufficiency of the datasets and allowed the identification of the main sources of uncertainty, highlighting aspects that require further investigation. The overall dataset was found to be sufficient in terms of reliability and spatiotemporal cohesion. However, it lacked in completeness, showing that there are still large areas of the Aegean that remain understudied, while further research is needed to elucidate the distribution patterns and conservation status of several ecological features; especially the less charismatic ones and those found in waters deeper than 40 m. Moreover, existing conservation measures appear to be inadequate to safeguard biodiversity. Only 2.3% of the study area corresponds to designated areas for conservation, while 41 of the ecological features are underrepresented in these areas. Considering the high geomorphological complexity and transnational character of the Aegean Sea, this study does not offer a complete account of the multifaceted diversity of this ecoregion. Instead, it represents a significant starting point and a solid basis for the development of systematic conservation plans that will allow the effective protection of biodiversity within an adaptive management framework.